1104 Effects of Belimumab (BEL) on Renal Outcomes in Patients (pts) With Relapsed and Newly Diagnosed Active Lupus Nephritis (LN). (14th December 2022) - Anders, Hans-Joachim; Rovin, Brad H; Zhao, Ming-Hui; Malvar, Ana; Hiromura, Keiju; Leone, Angela Jones-; Gonzalez-Rivera, Tania; Gilbride, Jennifer; Madan, Anuradha; Green, Yulia; Roth, David A
Abstract : Background: Despite standard therapy (ST) for LN, only 20–40% of pts achieve Complete Renal Response (CRR) at 0.5–1 year and 20–25% relapse in 3–5 years. Achieving CRR is often more difficult in relapsed patients than in de novo patients. The aim of this study was to assess effects of BEL on renal outcomes in relapsed and newly diagnosed pts with LN. Methods: A post hoc analysis of the Phase 3, randomized, double-blind, 104-week BLISS-LN study (GSK BEL114054; NCT01639339 ) was performed. Pts with active LN received monthly intravenous (IV) BEL 10 mg/kg or placebo (PBO) + ST. Randomization was stratified by induction regimen: high dose corticosteroids (HDCS) + cyclophosphamide (CYC), followed by azathioprine + low-dose corticosteroids (LDCS), or HDCS + mycophenolate mofetil (MMF), followed by MMF + LDCS. We assessed Primary Efficacy Renal Response (PERR; uPCR ≤0.7; eGFR no more than 20% below pre-flare value or ≥60 ml/min/1.73m 2 ; no rescue therapy) and CRR (uPCR <0.5; eGFR no more than 10% below pre-flare value or ≥90 ml/min/1.73m 2 ; no rescue therapy) at Week 104 and time to renal-related event or death in relapsed vs newly diagnosed pts. Results: Of 446 pts included in this analysis, 150 had relapse of LN and 296 were newly diagnosed. Positive effects of BEL vs PBO on PERR and CRR were noted in both subgroups but were numerically greater in relapsed vs newly diagnosed pts (table 1). BEL-treated pts had a lower risk at any time of experiencing a renal-related event or death vs PBO in both subgroups (table 1). Conclusions: These data suggest BEL improved PERR and CRR rates more potently in relapsed pts, in which PERR and CRR were substantially less frequent compared with newly diagnosed LN. Acknowledgement: Abstract 1 reprinted from ASN Kidney Week, October 25–November 7, 2021. Reference: Hans-Joachim Anders, Brad Rovin, Ming-Hui Zhao, Ana Malvar, Keiju Hiromura, Angela R Jones- Leone, Tania Gonzalez Rivera, Jennifer Gilbride, Anu Madan, Yulia Green, David Roth. Effects of Belimumab (BEL) on Renal Outcomes in Patients With Relapsed and Newly Diagnosed Active Lupus Nephritis (LN). J Am Soc Nephrol. 2021;32 :48. Funding: GSK. Editorial assistance with encore abstract development was provided by Paragon, UK (funded by GSK). Disclosures: HJA has received consultancy fees from GSK, Novartis, AstraZeneca, Janssen, Kezar, Bayer, PreviPharma, Idorsia and Boehringer, and honoraria from GSK, Novartis, AstraZeneca, Janssen, Kezar, Bayer, PreviPharma, Idorsia, Boehringer, Lilly; is a Scientific Advisor/Membership for ERA-EDTA and an Associated editor at JASN and NDT. BHR has received consultancy fees from GSK. MHZ has received consultancy fees from GSK, AstraZeneca and Roche. A Malvar has received consultancy fees from GSK and Roche. KH has received consultancy fees from GSK. AJL, TGR, JG, A Madan, YG and DAR are employees of GSK and hold stocks and shares in the company.